Management of fluid balance in the very immature neonate. Issue 2 (1st March 2004) - Modi, N
Abstract : Preterm birth requires rapid adaptation from a liquid to a gaseous, low humidity environment. There are several ways in which this can be facilitated. The management of sodium and water balance is considered here.